Observational study on calf carcasses in 2 processing plants for animal byproducts in Germany - M. Sickinger; A. Wehrend (JDS Communications)
In the dairy industry, surplus calves have been reported to be especially prone to poor welfare on farms and to inappropriate killing of male calves for economic reasons. Therefore, this study aimed to examine calf carcasses for evidence of inappropriate killing and diseases that may have caused prolonged suffering and unnecessary pain in the course of their lives. Our study was conducted during March 2022 and from April to May 2023 in 2 animal byproduct processing plants, where we carried out external inspections of the carcasses to record the sex of the animals and check for the presence of identification marks. We paid particular attention to findings relevant to animal welfare that suggested improper killing or unnecessary suffering and pain in the animals. The examinations included observations on the skinned carcasses (in plant 1), as well as on carcasses in the blanket, the opening of the trachea, and the carpal and tarsal joints (i.e., partial necropsy). In total, 981 calves from dairy cattle and beef cattle herds were examined on 19 delivery days. This encompassed 450 calves at the first location and 531 at the second location. In total, 515 calves were male and 465 were female. The sex of one animal could not be determined because of the nutritional trace on the carcass. Ear tags were not inserted in 588 calves. Five of the 588 calves initially had ear tags. Ear tags were detected in 393 calves. At partial necropsy, 18 animals were diagnosed with profound emaciation. Additionally, arthritis existed in 9 animals. Chronic diseases other than arthritis were observed in 27 (2.8%) of 981 animals. Arthromyodysplastic syndrome was diagnosed in 26 animals. Fractures were found in 38 animals, of which only 3 cases occurred antemortem. The remaining 35 cases of fracture occurred postmortem as a result of transportation. No animal had signs of improper obstetric care. Amniotic fluid was detected in the lumen of the trachea of 122 stillborn calves (i.e., death sub natu). In contrast to the situation reported in pigs, no evidence existed in the 2 animal byproduct processing plants investigated for calf carcasses that inappropriate killing and diseases leading to prolonged suffering and unnecessary pain before death represented systemic problems. No fundamental need for routine testing of animal carcasses existed in either animal byproduct processing plant.